E –Payment System Using Visual and Quantum Cryptography. (2016) - Shemin, P.A.; Vipinkumar, K.S.
Abstract: In recent years E-shopping gained a tremendous growth due to its benefits. Even though benefits of E-shopping are considerable, it creates some security threats such as debit, credit card fraud, phishing etc. In this paper we introduce an E-payment system that provides an unrivaled security using visual and quantum cryptography. Visual cryptography hides the details of customer by generating shares whereas Quantum cryptography secures the transmission of one time password . Image steganography embeds the share with one time password which results in secure transmission of share to bank. Proposed approach guarantees unconditional security than traditional E-payment system by using two important cryptographic techniques.